Determinants of trust: the role of personal experiences - Frederik Schwerter; Florian Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2019)
Social interactions pervade daily life and thereby create an abundance of social experiences. Such personal experiences likely shape what we believe and who we are. In this paper, we ask if and how personal experiences from social interactions determine individuals' inclination to trust others? We implement an experimental environment that allows us to manipulate prior social experiences—either being paid or not being paid by a peer subject for a task—and afterwards measure participant's willingness to trust others. We contrast this situation with a control condition where we keep all aspects of the prior experiences identical, except that we remove the social dimension. Our key finding is that after positive social experiences, subjects' willingness to trust is substantially higher relative to subjects who made negative social experiences. No such effect is obtained in the control condition where we removed the social aspect of experiences. Findings from a difference-in-difference analysis confirm this pattern. Our results cannot be explained by rational learning, income effects, pay or social comparison related mood, disappointment aversion and expectations-based or social reference points. Delving into the underlying mechanisms, we provide evidence that non-standard belief patterns are an important driver of experience effects.
Keywords: C91; D03; D81; 330; determinants of trust; experiences; beliefs; non-standard learning; experiments